1996
DOI: 10.1002/chin.199621261
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Stereocontrol in Organic Synthesis Using the Diphenylphosphoryl Group

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Our in vitro analysis, designed to simulate oral conditions of chewing, demonstrated that chewing LAN or AN with slaked lime decreased the levels of muscarinic esters, arecoline and guvacoline via hydrolysis and increased the levels of the carboxylic GABAergic uptake inhibitor metabolites, arecaidine consistent with previous studies. 4 , 5 , 45 , 46 , 47 , 48 Guvacine levels were increased in assays of AN and not significantly increased in assays of LAN. Other functionally active unknown compounds may have been produced by hydrolysis although the mutagenic compound, nitrosoguvacoline, was not detected.…”
Section: Discussionmentioning
confidence: 83%
“…Our in vitro analysis, designed to simulate oral conditions of chewing, demonstrated that chewing LAN or AN with slaked lime decreased the levels of muscarinic esters, arecoline and guvacoline via hydrolysis and increased the levels of the carboxylic GABAergic uptake inhibitor metabolites, arecaidine consistent with previous studies. 4 , 5 , 45 , 46 , 47 , 48 Guvacine levels were increased in assays of AN and not significantly increased in assays of LAN. Other functionally active unknown compounds may have been produced by hydrolysis although the mutagenic compound, nitrosoguvacoline, was not detected.…”
Section: Discussionmentioning
confidence: 83%